The multifaceted impact of US trade policy on financial markets - Lukas Boer; Lukas Menkhoff; Malte Rieth (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
We study the multifaceted effects of trade policy shocks on financial markets using a structural vector autoregression identified via event day heteroskedasticity. We find that restrictive US trade policy shocks affect US and international stock prices heterogeneously, but generally negatively. They increase market uncertainty, lower US interest rates, and lead to an appreciation of the US-Dollar. The effects are significant for several weeks or quarters. Decomposing the trade policy shocks further suggests that trade policy uncertainty dominates tariff level effects. Chinese trade policy shocks against the US further hurt US stocks.
Keywords: C32; F13; F51; G10; 330; Trade policy shock; structural VAR; stock prices; exchange rates; interest rates; heteroskedasticity